Pengembangan Strategis Pemasaran Minyak Esensial Sebagai Media Relaksasi Bagi Konsumen Urban - Falih Ijlal Wicaksono (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Mental health is an important issue in the midst of dynamic and stressful urban society. One of the developing non-medical approaches is the use of essential oil-based aromatherapy as a relaxation medium. This study aims to analyze the development of essential oil product marketing strategies aimed at urban consumers. Through a qualitative descriptive approach, this study describes how market segmentation, targeting, and positioning strategies (STP), and marketing mix (4P) can be applied effectively to increase consumer awareness of the benefits of aromatherapy. The Euromonitor survey (2023) shows that 70% of consumers in the Southeast Asia region prefer natural health products that support emotional balance. In addition, Nielsen (2022) reports that 65% of urban consumers use social media as the main source of information on health and relaxation products. The results of the analysis show that marketing strategies that prioritize emotional narratives, consumer education, and digital media optimization have proven relevant in building brand value and engagement. Thus, the development of essential oil marketing strategies not only supports business growth but also makes a positive contribution to the quality of life of urban communities.